The settlement structure of the North-Western part of the Carpathian Basin during the middle and late Early Iron Age. The Early Iron Age settlement at Győr-Ménfőcsanak (Hungary, Győr-Moson- Sopron county) - Ďurkovič, Éva (Dissertationes Archaeologicae, 2017)
x